國中公民科初任教師學科教學知識發展之研究 The Pedagogical Content Knowledge Development of Junior High School Beginning Teachers in Civic Education - 黃品瑄 Pin-Hsuan Huang; 湯仁燕 Ren-Yen Tang (National Changhua University of Education, 2017)
初任教師在離開師培機構、進入教育現場之後，往往容易深陷初任教職的泥淖，產生所謂現實的震撼。他們在投入教學的過程中，透過不斷的調整與轉化，慢慢摸索與試圖建立屬於自己的學科教學知識，這樣的歷程值得深究。為探討國中公民科初任教師學科教學知識之發展歷程，本研究採用質性研究取向，以深度訪談為主要蒐集資料方法，輔以觀察及文件分析，探討兩位公民科教師的學科教學知識，希冀藉由本研究之結論與建議，對相關研究者或教學者有所啟發，亦期能作為師培單位之參考。 After graduating from teacher preparation institutions, beginning teachers often get stuck in their school job, and experience reality shock. Through several adjustments and changes in their teaching processes, beginning teachers gradually explore and establish their own pedagogical content knowledge (PCK). With two beginning junior high school teachers as the subjects, the purpose of this research is to explore how they develop their PCK in the area of civic education. Adopting a qualitative approach, the data sources in this study included classroom observation, interviews and documents. It is hoped that the findings and suggestions of this study will be of interest to other teachers and researchers, and also provide valuable information for teacher education institutions.